2021
DOI: 10.3390/s21113649
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Movement Events of Long-Track Speed Skating Using Wearable Inertial Sensors

Abstract: Inertial measurement units (IMUs) have been used increasingly to characterize long-track speed skating. We aimed to estimate the accuracy of IMUs for use in phase identification of long-track speed skating. Twelve healthy competitive athletes on a university long-track speed skating team participated in this study. Foot pressure, acceleration and knee joint angle were recorded during a 1000-m speed skating trial using the foot pressure system and IMUs. The foot contact and foot-off timing were identified using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…The accuracy of temporal and spatial parameters in skating (on average less than 4% of relative error) in this study was comparable with those reported in gait analysis (less than 2% relative error 29 , 42 ). Also, almost the same accuracy in calculating ST has been obtained compared to the other studies on long-track speed skating (3.6%) 11 . Finally, the accuracy of CT and ST obtained by IMU in this study was comparable with those reported in a previous study on ice skating 15 investigating the accuracy of CT and ST estimated on the real ice (on average, 1% and 2%, respectively).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The accuracy of temporal and spatial parameters in skating (on average less than 4% of relative error) in this study was comparable with those reported in gait analysis (less than 2% relative error 29 , 42 ). Also, almost the same accuracy in calculating ST has been obtained compared to the other studies on long-track speed skating (3.6%) 11 . Finally, the accuracy of CT and ST obtained by IMU in this study was comparable with those reported in a previous study on ice skating 15 investigating the accuracy of CT and ST estimated on the real ice (on average, 1% and 2%, respectively).…”
Section: Discussionsupporting
confidence: 75%
“…However, the application of these instruments is limited since they are not available in every ice rink, and their captured volume is confined to a small part of the ice rink, which can disrupt the natural skating patterns of ice skaters 8 – 10 . Thus, wearable and garment-embedded technologies are preferable for on-ice skating performance assessments 11 13 .…”
Section: Introductionmentioning
confidence: 99%
“…According to the survey, world-class speed skating long-distance athletes have a good stamina distribution strategy in the 3000m competition. They have the characteristics of fast starting speed, strong mid-range speed maintenance ability and small back-range speed reduction difference [24][25]. However, most athletes have an elevated level of energy metabolism in the body during the middle and late stages due to the alternation between the anaerobic and aerobic energy supply systems, as well as a signi cant increase in the rate of lower limb work.…”
Section: Discussionmentioning
confidence: 99%
“…However, inertial sensors eliminate these limits by wearing them directly on the body. Some studies found that the inertial sensors had a high consistency (>0.9) with the gold standard [ 70 ]. Hence, the motion information obtained by the inertial sensors during training can be applied to evaluate the performances of athletes in training, and provide actionable data for athletes, coaches, and researchers to improve training plans, and equipment.…”
Section: Biophysical Signalsmentioning
confidence: 99%